Trade and Labour Standards - Theory, New Empirical Evidence, and Policy Implications - Vivek H. Dehejia; Yiagadeesen Samy (Center for Economic Studies and ifo Institute (CESifo), 2002)
Recent trade negotiations, both at the regional and multilateral level, have seen a resurgence of the issue of trade and labour standards. As the world economy becomes increasingly globalised and the volume of world trade flows keeps increasing between the North and the South, it is very likely that the interaction of labour standards and international trade will continue to remain high on the agenda of future trade talks. Labour interests in high-standards countries argue that low labour standards are an unfair source of comparative advantage, and that increasing imports from low-standards countries will have an adverse impact on wages and working conditions in high-standards countries, thus leading to a race to the bottom of standards. For low-standards countries, there is the fear that this is just a form of disguised protectionism and that the imposition of high labour standards upon them is equally unfair since it will erode their competitiveness, the latter being largely based on labour costs. Our objective in the present paper is to cast some light on the above debate from both a theoretical and empirical perspective. In particular, we first discuss some possible theoretical links between labour standards and comparative advantage through their effects on the terms of trade. We then investigate empirically the effects of labour standards on export performance and foreign direct investment flows. Overall, our empirical results suggest that caution should be exercised before drawing broad conclusions on the magnitude and direction of these effects. We conclude by presenting policy implications of our analysis.
Keywords: 330